Exploring factors influencing the uptake of Kangaroo mother care: key informant interviews with healthcare workers - Wai Cheng Foong; Siew Cheng Foong; Jacqueline J. Ho; Pek Yong Tan; Jen Jen Leong; Mehala Baskaran (BMC Pregnancy and Childbirth)
Abstract Introduction Kangaroo mother care (KMC), besides reducing mortality, offers significant benefits for preterm and low birth weight infants, prompting the World Health Organization to reaffirm a strong recommendation for KMC as essential care. However, uptake remains unsatisfactory due to challenges in implementation and sustainment. Objectives To explore factors influencing KMC implementation by healthcare workers (HCWs) and identify interventions for improvement. Method Using purposive sampling, we conducted key informant interviews with HCWs from neonatal wards and neonatal intensive care units (NICU) of two hospitals. Data were transcribed and categorised based on the Triandis framework. Results KMC was not regarded as an essential component of early management for preterm infants. The challenge was not a lack of awareness but the difficulty integrating KMC into existing workflows while balancing other clinical responsibilities. Heavy workloads resulted in KMC sidelined in favor of routine ward tasks. Junior HCWs lacked the autonomy to initiate KMC without senior approval. Even HCWs eager to advocate for KMC faced significant frustrations. Overcrowded wards, limited resources, and staff shortages made KMC feel like an added burden. Additionally, they struggled to persuade reluctant parents and feared repercussions if unexpected complications arose when parents performed KMC. The lack of KMC in key performance indicators further compounded these challenges, hindering its widespread implementation. Conclusion For KMC implementation to improve, it must be recognized as an essential part of neonatal care, with incentives for promoting KMC. Support for staff and adequate space in the wards, ideally by having mother-infant wards and NICUs are also necessary. Trial registration This study was registered with the National Medical Research Registry (NMRR-17-2984-39191).